Economic Assimilation of the "Third Generation": An Intergenerational Mobility Perspective on Immigration and Integration - Aslan Zorlu; Wouter van Gent (Institute of Labor Economics (IZA), 2020)
This paper examines ethnic disparities in intergenerational economic mobility for the children of second-generation "migrants." Using rich register data for adult children aged 20 to 30, we provide empirical evidence on the economic assimilation outcomes of the descendants of immigrants who mainly arrived in the Netherlands in the post-World War II period. Acknowledging a high degree of diversity in the starting positions of immigrants associated with their dominant migration motives, we estimate the Dutch-migrant group gap in incomes from an intergenerational mobility perspective. Our descriptive rank-rank analysis reveals significant ethnic disparities in absolute and relative intergenerational income mobility. The absolute mobility of the ethnic groups we study appears to have the following rank order: Moroccan, Turkish Surinamese, Indish, German, and Dutch. While a higher level of intergenerational transmission of parental income narrows the gap for Turkish and Surinamese children, it widens the gap for Indish and Moroccan children. Our decomposition analysis shows that the ethnic disparities found for the Moroccan, Turkish, and Surinamese third generation are entirely explained by their relatively young ages and associated unfavorable socioeconomic positions, and by their lower parental income levels.
Keywords: J15; J31; J61; 330; income; third generation; second generation; immigrants